Industrial Relations Concepts in the USA - Barbash, Jack (Relations industrielles / Industrial Relations, 1991)
Industrial relations concepts are synthesized in order to make explicit the underlying values of industrial relations at a particular stage of its development. It is argued that industrial relations' underlying value is the human essence of labor as a commodity or factor of production and labor's right to equity in the employment relationship. Labor's human essence and employment equity are seen as the defining themes of industrial relations. Labor problems arise out of the adverse effects of industrialism on the human condition. Industrial relations' problem-solving aims to ameliorate these effects through applications of the equity principle in the employment relationship. Leading concepts of industrial relations are structured in a sort of logic or sequence of propositions that are summarily stated in the form of a syllabus as an expository device.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Labor Unions; Labor negotiations; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Unions